A 2, 2′-bipyridine-containing covalent organic framework bearing rhenium(i) tricarbonyl moieties for CO2 reduction. Issue 48 (30th November 2018) - Popov, Damir A.; Luna, John M.; Orchanian, Nicholas M.; Haiges, Ralf; Downes, Courtney A.; Marinescu, Smaranda C.
Abstract : The reduction of CO2 into higher energy products such as carbon-based fuels and feedstocks is an attractive strategy for mitigating the continuous rise in CO2 emissions associated with the growing global energy demand. Abstract : The reduction of CO2 into higher energy products such as carbon-based fuels and feedstocks is an attractive strategy for mitigating the continuous rise in CO2 emissions associated with the growing global energy demand. Rhenium tricarbonyl complexes bearing 2, 2′-bipyridine (2, 2′-bpy) ligands are well-established molecular electrocatalysts for the selective reduction of CO2 to CO. Construction of efficient devices for this electrochemical process requires the immobilization of electrocatalysts to electrode surfaces. To integrate Re(2, 2′-bpy)(CO)3 fragments into a covalent organic framework (COF), Re(5, 5′-diamine-2, 2′-bpy)(CO)3 Cl (1 ) was synthesized and electrochemically investigated. Complex1 is an active and selective electrocatalyst for the reduction of CO2 to CO with excellent faradaic efficiency (99%). The presence of the amine substituents leads to a destabilization of the π* orbital of the 5, 5′-diamine-2, 2′-bpy ligand with respect to the metal center. Therefore, 1 requires more negative potentials (−2.47 V vs. Fc +/0 ) to reach the doubly reduced catalytically active species. DFT studies were conducted to understand the electronic structure of1, and support the destabilizing effect of the amine substituents. The Re-2, 2′-bpy fragments were successfully integrated into a COF containing 2, 2′-bpy moieties (COF-2, 2′-bpy) via a post-metallation synthetic route to generate COF-2, 2′-bpy-Re. A composite of COF-2, 2′-bpy-Re, carbon black, and polyvinylidene fluoride (PVDF) was readily immobilized onto glassy carbon electrodes and electrocatalytic CO2 reduction to CO was observed at −2.8 V vs. Fc 0/+, with a faradaic efficiency of 81% for CO production.